Arthroscopic Superior Capsule Reconstruction for Cuff Tear Arthropathy (Hamada Grade 5): A Case Report. Issue 4 (October 2020) - Inoue, Kosuke; Kenmoku, Tomonori; Nakawaki, Mitsufumi; Tazawa, Ryo; Matsumoto, Mitsuyoshi; Takaso, Masashi
Abstract : Case: We performed arthroscopic superior capsule reconstruction (ASCR) for cuff tear arthropathy (CTA) with humeral head deformity. A 62-year-old man presented with severely limited shoulder motion and recalcitrant omalgia. He had a history of dental implant removal due to metal allergy, and his Constant score was 21 points. We diagnosed CTA with Hamada classification grade 5 and performed ASCR to avoid allergic reactions. Severe night pain improved within 1 week of ASCR, and his Constant score after 2 years was 74 points. Conclusion: ASCR may be an effective alternative treatment for patients with CTA with humeral head deformity.